Application of an Optimized Direct Lysis Method for Viral RNA Extraction Linking Contaminated Dates to Infection With Hepatitis A Virus - Rajiuddin, Sheikh Md; Midgley, Sofie Elisabeth; Jensen, Tenna; Müller, Luise; Schultz, Anna Charlotte (Frontiers in Microbiology, 2020)
Consumption of dates have not been considered a common risk of hepatitis A virus (HAV) infection. In January 2018, an outbreak of hepatitis was identified with cases resident in all regions of Denmark. All the detected strains belonged to HAV genotype 3A. Epidemiological investigations through patients’ interviews, case-control and trace-back studies pointed towards different batches of dates from a single producer as the vehicle of infection. Boxes of dates from suspected batches were collected from patients’ homes and analyzed using a recently reported optimized direct lysis method, consisting of simultaneous viral RNA elution and extraction from dates followed by purification of the nucleic acids. Extracts were analyzed for HAV and norovirus (NoV) RNA using RT-qPCR, while detected HAV were genotyped by Sanger sequencing. Among 20 nucleic acid extracts representing eight batches of dates, RNA of HAV (9.3×102 genome copies/g) and NoV genogroup (G)II (trace amounts) were detected in one batch, while NoV GII RNA (trace amounts) was detected in another. Average extraction efficiency of spiked process control murine norovirus was 20±13 % and the inhibitions of RT-qPCR detection of NoV GI, NoV GII and HAV were 31±34, 9±9 and 3±7 %, respectively. The HAV genome detected in the dates matched by sequence 100 % to the HAV genotype 3A detected in stool samples from cases implicated in the outbreak. This confirmed, to our knowledge, for the first time a sequence link between HAV infection and consumption of contaminated dates, suggesting dates to be an important vehicle of HAV transmission.